VALUASI EKONOMI SUMBERDAYA PERIKANAN TANGKAP DI PERAIRAN NEGERI WAAI KECAMATAN SALAHUTU MALUKU - Angel Ruban; Saiful Saiful; Gratia Dolores Manuputty (Universitas Pattimura, 2021)
The potency of capture fishery resources at Waters of Waai allows the fishermen to utilize it in order to support the community economy. However, if it is not carried out following the principles of sustainable fisheries, it can cause problems such as overfishing, overcapacity and resource degradation. The study aims to estimate the economic value of capture fishery resources at Waters of Waai as one of the basic to determine the sustainable fisheries management. Primary data collection was carried out on 7 purse seine business owners and analyzed using the effect on production (EOP) approach. The result found that the demand functions of capture fishery resources at Waters of Waai were influenced by price (X1), income (X2), age (X3), business experience (X4) and number of dependants (X5). Amount of consumer surplus is Rp 642.113.972 per fisherman per year and the economic value of capture fishery resources at Waters of Waai is Rp 55.256.403 per hectare per year.